Resource recovery from livestock waste: cases and business models from the Global South - Taron, Avinandan; Sathiskumar, Abinaya; Mateo-Sagasta, Javier; Singha, R.; Dejen, Z. A.; Chipatecua, G. P.; Bastidas, R. R. (International Water Management Institute, 2025)
Livestock waste poses significant environmental and public health challenges in low- and middle-income countries (LMICs), particularly through water pollution and the spread of infectious diseases. Nutrient-rich runoff from this waste contributes to eutrophication, while pathogens such as Escherichia coli and Salmonella contaminate surface waters, posing serious risks to human and animal health. Yet, this waste stream also presents opportunities for circular bioeconomy solutions. When converted into biogas, organic fertilizer, or aquaculture feed, livestock waste can help mitigate environmental harm, generate energy, enhance soil health, and support rural livelihoods. This report synthesizes findings from 135 global cases and further presents an in-depth analysis of 26 livestock waste recovery initiatives to highlight diverse models and regional strategies. The available data show that in Latin America and Sub-Saharan Africa, biodigestion is primarily used for household or commercial energy and revenue generation. South and Southeast Asian countries, meanwhile, focus on producing compost, aquaculture feed, and vermicompost. Government support, including subsidies, incentives, and technical assistance, often underpins these efforts, sometimes in collaboration with the private sector. Three broad business models emerge: (i) energy and biofertilizer recovery, (ii) soil nutrient recovery, and (iii) food nutrient recovery for aquaculture. Government-led community initiatives tend to exhibit higher economic feasibility, while private-sector models tend to scale better commercially. With average payback periods of five to six years and cost-benefit ratios ranging from 1 to 2, these models offer scalable solutions—when backed by enabling policies, institutional coordination, and localized feasibility assessments—to promote sustainable rural development and address critical environmental risks.